RAMAN SPECTROSCOPY CHARACTERIZATION OF PULSED LASER DEPOSITION GROWN ZNTE THIN FILMS ON SAPPHIRE SUBSTRATE - Rezapoor, Fatemeh (My University, 2015)
Compound semiconductors are the foundation of many electronic and optoelectronic devices. As a result semiconductor epitaxy can be viewed as the first significant step in device engineering. Accurate and reliable characterization methods are needed to measure semiconductor properties including optical, electrical, vibrational and crystal structure. In this thesis, the epitaxy of ZnTe thin films on sapphire substrate by Pulsed Laser Deposition system at different growth temperatures is studied. The texture analysis is inspected by Two Dimensional X-Ray Diffraction. The lattice constant of the films and strain studies are investigated by High Resolution X-Ray Diffraction. UV-Vis spectroscopy is applied to find absorption edge in ZnTe thin film in order to estimate optical bandgap. These common characterization methods reveal the great effect of growth temperature on crystalline and optical properties of ZnTe thin films. In addition, Raman spectroscopy is used for the first time in the Preston's group to examine vibrational modes in ZnTe thin films. This new characterization method, which is the main focus of this thesis, uncovers some new features of ZnTe thin films not accessible through other techniques. In this thesis, optimum experimental conditions, instrumentation and data analysis of Raman observations in thin films are studied in detail. The final results are in good agreement with other characterization methods and they can justify crystalline and optical observations. These results demonstrate that Raman spectroscopy is a non-destructive characterization method applicable to thin film analysis.
RAMAN CHARACTERIZATION OF PLD GROWN ZNTE FILMS ON SAPPHIRE
Keywords: Raman Spectroscopy; Epitaxy; Thin Films; Pulsed Laser Deposition; ZnTe; Crystal Structure; Vibrational modes; Semiconductor growth